2019
DOI: 10.1021/acs.analchem.8b04762
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Calibration Quantitative Mass Spectrometry Imaging for Accurately Mapping Analytes across Heterogenous Biotissue

Abstract: It is highly challenging to quantitatively map multiple analytes in biotissues without specific chemical labeling. Quantitative mass spectrometry imaging (QMSI) has this potential but still poses technical issues for its variant ionization efficiency across a complicated, heterogeneous biomatrices. Herein, a self-developed air-flow-assisted desorption electrospray ionization (AFADESI) is introduced to present a proof of concept method, virtual calibration (VC) QMSI. This method screens and utilizes analyte res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 44 publications
(53 reference statements)
0
35
0
Order By: Relevance
“…Analyte response-related endogenous metabolite ions were chosen as native internal standards to solve the difficult problem of evenly adding the IS in tissues. This method was demonstrated to be suitable for accurately mapping the quantity of analytes in the whole body and the linearity of the standard curve calibrated with VC was as good as using isotopic IS (Figure 7H) [140]. (2021) American Chemical Society.…”
Section: Metabolitesmentioning
confidence: 94%
See 1 more Smart Citation
“…Analyte response-related endogenous metabolite ions were chosen as native internal standards to solve the difficult problem of evenly adding the IS in tissues. This method was demonstrated to be suitable for accurately mapping the quantity of analytes in the whole body and the linearity of the standard curve calibrated with VC was as good as using isotopic IS (Figure 7H) [140]. (2021) American Chemical Society.…”
Section: Metabolitesmentioning
confidence: 94%
“…(H) Standard curves obtained with different calibration methods. Reprinted with permission from the authors of [140]. Copyright (2019) American Chemical Society.…”
Section: Metabolitesmentioning
confidence: 99%
“…Later, the same group demonstrated that virtual calibration is just as effective as using SIL ISs for pixelby-pixel calibration (Fig. 3) [116]. The presented method utilized analyte response-related endogenous metabolite ions from each mass spectrum as native ISs.…”
Section: Tissue Imagingmentioning
confidence: 97%
“…(h) Final quantitative result by virtual calibration-QMSI which is cross-validated with a previously reported tissue extinction coefficient-QMSI method. Reproduced from reference [116]. Copyright 2019 American Chemical Society extraction efficiency is dependent on sample properties, making quantitation difficult.…”
Section: Tissue Imagingmentioning
confidence: 99%
“…Historically, quantitation of AMS data has proven to be challenging due to reproducibility, especially the uniform introduction of standards on to tissue surfaces and matrix ion suppression effects, 188,189 although improved techniques have been reported recently. 190,191 For the future, advances in database metabolite identification, the ability to quantify the data, and particularly to view drug distribution and metabolic profile changes over time in a continuous manner, would provide important information regarding catabolic and biosynthetic pathways, as well as the mechanisms and timing of metabolite translocation in plant and animal tissues. Enhancement in spatial resolution requires a corresponding increase in sensitivity.…”
Section: Mass Spectrometry Imagingmentioning
confidence: 99%